PRODUCTIVITY OF GRASS Pennisetum purpureum cv. Mott FEDWITH FOLIAR FERTILIZER AT DIFFERENT DOSES - J., Tampubolon; Kusumawati, N. N. C.; Witariadi, N. M. (Jurnal Peternakan Tropika, 2024)
The study aimed to determine the productivity of Pennisetum purpureum cv. Mott fed with foliar fertilizer at different dosages. The study was conducted in a greenhouse on Jalan Raya 140 Sading No.93, Mengwi Badung, starting from July to September 2022. The experimental design used was a complete randomized design (RAL) with four treatments and seven repeats. The four treatments are: dose 0 kg ha-1 (P0), dose 200 kg ha-1 (P1), dose 400 kg ha-1 (P2), dose 600 kg ha-1 (P3). The variables observed are growth variables, yield variables and growth characteristic variables. Foliar fertilizer treatment at a dose of 600 kg ha-1 (P3) was able to increase the number of leaves of elephant kate grass. Plant height and the number of saplings fertilized with foliar fertilizer have not been able to show an increase, as well as the variables of dry weight of leaves, dry weight of stems, dry weight of roots, and total dry weight of forage give the same results. On the variables of plant height and number of saplings showed different results were not real. On the variable number of leaves showed markedly different results with all treatments. While the variables of dry weight of leaves, dry weight of stems, dry weight of roots, and total dry weight of forage showed different results were not real. Characteristics of growing grass Pennisetum purpureum cv. Mott on variable leaf area with foliar fertilizer treatment dose 600 kg ha-1 (P3) was able to increase leaf area and showed markedly different results. However, it has not been able to improve on the variable ratio of dry weight of leaves to stems and the ratio of total dry weight of forage to roots and showed results not significantly different. Based on the results of the study, it can be concluded that the use of foliar fertilizer has not been able to increase the productivity of elephant kate grass (Pennisetum purpureum cv. Mott) and doses of 600 kg ha-1 (P3) showed the best likely results.